How Korean Language Arts Teachers Adopt and Adapt Open Educational Resources: A Study of Teachers’ and Students’ Perspectives - SuBeom Kwak (International Review of Research in Open and Distributed Learning, 2017)
Since 2005, open educational resources (OER) have played a key role in K-12 education in South Korea; so far, however, there has been little discussion about OER efficacy in South Korean K-12 education. In the meantime, South Korean education has been attracting a lot of interest around the world. Former U.S. President Obama’s comments about South Korean education might also be caused by South Korean students’ academic performance evaluated by international large-scale assessments such as the Program for International Student Assessment (PISA). This article uses an ethnographic perspective to explore the experiences of teachers and students in the Korean context. The analysis of the findings shows how teachers adopt and adapt OER for their 12th grade (the final year of secondary school) Korean language arts classes. Through classroom observations, interviews, and questionnaires, this exploration revealed that nearly 92% of the students perceived OER as beneficial to their studies and that teachers were spurred on to orchestrate differentiated instructional plans by OER. We argue that there is significant value to using OER in the formal educational curriculum, but that a lack of knowledge of how to adapt OER restricts how their potential is realized in practice. We identify implications for maximizing OER adaptation and successful usage of OER in K-12 education.